2000
DOI: 10.1007/bf03027956
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug errors in anesthesia, and the impact of coloured syringe labels

Abstract: Purpose: To describe the frequency and pattern of drug errors in clinical anesthesia, and to evaluate whether a change to colour coded syringe labels, along with education, could reduce the problem of drug errors. Methods:We prospectively recorded anesthesia-related information from all anesthetic cases for 36 mo, totally 55,426 procedures. Intraoperative problems, including drug errors, were recorded. After eighteen months we changed to colour coded syringe labels, and the effect of this change and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
152
2
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(165 citation statements)
references
References 38 publications
5
152
2
6
Order By: Relevance
“…[1][2][3][4][5] Complex surgical procedures and patients with significant comorbidities often require therapeutic interventions with infrequently used medications utilized under dynamic conditions, all contributing to higher medication error rates when compared with cases with lower surgical complexity. 6,7 The inexperience of trainees in the specialty may also lead to a higher frequency of medication errors in teaching programs, yet there are few data to support this claim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Complex surgical procedures and patients with significant comorbidities often require therapeutic interventions with infrequently used medications utilized under dynamic conditions, all contributing to higher medication error rates when compared with cases with lower surgical complexity. 6,7 The inexperience of trainees in the specialty may also lead to a higher frequency of medication errors in teaching programs, yet there are few data to support this claim.…”
Section: Introductionmentioning
confidence: 99%
“…Although Fasting and Gisvold reported that anesthesiologists have been involved in at least one medication error/ pre-error, most medication errors were deemed inconsequential. 5 Factors associated with medication errors/ pre-errors occurring within the operating room include personal distractions; production pressure; inadequate communication between medical caregivers; exposure to new, unexpected, or unfamiliar medication vials or labels; and misread/look-alike medication vials or ampules. 1,3,4,10 The aim of this prospective unblinded observational study was to determine whether the type of surgical case, the American Society of Anesthesiologists' (ASA) physical status classification, the level of experience of the anesthesia provider, or other factors impact the frequency and reporting of medication errors/pre-errors in a tertiary care academic teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…6 The focus of this current review is on strategies that are currently being engineered into care delivery systems to reduce drug-related errors in anesthetic practice. Such errors, which occur at a rate of about 1 per 130-450 patients, [7][8][9][10][11] are associated with increases in morbidity, mortality, and the costs of hospital care. [8][9][10][11][12] Fortunately, most anesthetic-related errors are inconsequential; however, some lead to substantial or permanent injury and even death.…”
Section: Résumémentioning
confidence: 99%
“…Such errors, which occur at a rate of about 1 per 130-450 patients, [7][8][9][10][11] are associated with increases in morbidity, mortality, and the costs of hospital care. [8][9][10][11][12] Fortunately, most anesthetic-related errors are inconsequential; however, some lead to substantial or permanent injury and even death. 8,13 In this review, we focus on systems designed to reduce medication errors in the operating room and highlight three Canadian initiatives: 1) systematic efforts to improve the labelling of drug ampoules and vials, 2) introduction of bar-coding in medication systems, and 3) novel tools for ''reconciliation'' or for accurate documentation and adjustment of patients' medication taken before and during their hospital stay.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation